2023
DOI: 10.2147/ijgm.s410015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sickle Cell Disease on Affected Individuals in Nigeria: A Critical Review

Abstract: Sickle cell disease is an autosomal recessive disorder of the beta-globin gene, with resultant deformation of the red blood cells and variable clinical outcomes. Nigeria is recognised as the country with the highest burden of sickle cell disease globally. This study aimed at critically reviewing available literature on impact of sickle cell disease in Nigeria. A literature search was carried out on four databases, and a total of 116 articles that met the inclusion criteria were included in the critical review.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…The role of SES in rate of 'under 5' mortality rate among SCD pediatric patients is not clearly defined and whether it plays a role in lower frequency of SCD among those in low SES needs to be verified. According to Adigwe et al [28] and Adigwe [29] the prevalence of SCD is 2-3% with adult prevalence of 0.05% in Nigeria. SCD is a significant contributor to Nigeria's 'under five' mortality figures.…”
Section: Discussionmentioning
confidence: 99%
“…The role of SES in rate of 'under 5' mortality rate among SCD pediatric patients is not clearly defined and whether it plays a role in lower frequency of SCD among those in low SES needs to be verified. According to Adigwe et al [28] and Adigwe [29] the prevalence of SCD is 2-3% with adult prevalence of 0.05% in Nigeria. SCD is a significant contributor to Nigeria's 'under five' mortality figures.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Amusa et al (2021) found that higher levels of pain were associated with poor pain management outcomes. Children who believed that their pain was related to sickle cell anemia experienced more musculoskeletal pain, frequent pain episodes, and a lower quality of life (Adigwe et al, 2023). Joseph et al (2021) found that coping strategies for some factors, like praying, had better pain management outcomes.…”
Section: Introductionmentioning
confidence: 99%